Correction: Metal–organic-framework derived Co–Pd bond is preferred over Fe–Pd for reductive upgrading of furfural to tetrahydrofurfuryl alcohol. Issue 35 (5th September 2022) - Pendem, Saikiran; Bolla, Srinivasa Rao; Morgan, David J.; Shinde, Digambar B.; Lai, Zhiping; Nakka, Lingaiah; Mondal, John
Abstract : Correction for 'Metal–organic-framework derived Co–Pd bond is preferred over Fe–Pd for reductive upgrading of furfural to tetrahydrofurfuryl alcohol' by Saikiran Pendem et al., Dalton Trans., 2019, 48, 8791–8802, ; https://doi.org/10.1039/C9DT01190K .